Question

To Prove' ( -a^{3} cos (B-C)+b^{3} cos (C-A)+C^{3} cos (A-B)=3 a b C )
Prof: ( L ) ", ( r ),
( sum a^{3} cos (B-C)=angle a^{2} cdot a cos (B-C)=sum a^{2}(2 R sin A) cos (beta-C) )

# = S + = 2 sin C cos (A-B) + 2 sin C cos C. 2R = 2 sin C [cos (A - B) + cos C] - R sin A si =2 sin C [cos (A - B) + cos [180° – (A + B)]] | rove that a'cos (B-C) + bº cos (C - A) + c cos (A - B) = 3abc. L.H.S = a'cos (B-C) + bcos (C - A) + cºcos (A - B) = Da cos (B-C) = Da’ a cos (B-C) = Sa?. 2R sin A.cos ( 5 2 D .

Solution